2022
DOI: 10.1186/s13023-022-02454-y
|View full text |Cite
|
Sign up to set email alerts
|

Thymectomy in ocular myasthenia gravis—prognosis and risk factors analysis

Abstract: Background Several retrospective studies have identified risk factors associated with ocular myasthenia gravis (OMG) generalization in non-surgical patients. However, the outcomes of OMG after thymectomy have not been investigated fully. This study aimed to explore the clinical predictors of post-thymectomy OMG prognosis. Methods We performed a retrospective review of OMG patients who underwent thymectomy at our institution from January 2012 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This reduction applied to patients with thymomatous and even more so to nonthymomatous myasthenia gravis. Another recent single center case series of 58 thymectomized patients with ocular myasthenia gravis from China found similar generalization rates of 22.4% after thymectomy, with a higher rate of conversions for thymomatous myasthenia gravis [38].…”
Section: Ocular Myasthenia Gravis and Thymectomymentioning
confidence: 80%
“…This reduction applied to patients with thymomatous and even more so to nonthymomatous myasthenia gravis. Another recent single center case series of 58 thymectomized patients with ocular myasthenia gravis from China found similar generalization rates of 22.4% after thymectomy, with a higher rate of conversions for thymomatous myasthenia gravis [38].…”
Section: Ocular Myasthenia Gravis and Thymectomymentioning
confidence: 80%
“…Despite lacking a significant association of age at onset and sex with the presence of thymoma in univariate analysis, both factors were still included in the multivariate analysis owing to the results from previous literature showing a higher prevalence of thymoma in a younger age group and in females. 14 Nevertheless, multivariate analysis showed that an AChR antibody titer ≥15.12 nmol/L (OR 4.97, 95% CI: 1.10-22.48; p = 0.037) was the only significant factor associated with the presence of thymoma (Table 4).…”
mentioning
confidence: 97%